2006
DOI: 10.1038/ncb1448
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator inhibitor-1 is a critical downstream target of p53 in the induction of replicative senescence

Abstract: p53 limits the proliferation of primary diploid fibroblasts by inducing a state of growth arrest named replicative senescence -a process which protects against oncogenic transformation and requires integrity of the p53 tumour suppressor pathway [1][2][3] . However, little is known about the downstream target genes of p53 in this growth-limiting response. Here, we report that suppression of the p53 target gene encoding plasminogen activator inhibitor-1 (PAI-1) by RNA interference (RNAi) leads to escape from rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
457
3
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 515 publications
(500 citation statements)
references
References 40 publications
30
457
3
2
Order By: Relevance
“…Accordingly, the p53 target gene p21 WAF , a cyclin-dependent kinase inhibitor, was efficiently induced upon TACC3 depletion, whereas expression of the p53-independent cyclin-dependent kinase inhibitor, p27 KIP , remained unchanged (Supplementary Figure 3a). Furthermore, TACC3 depletion correlated with increased levels of cyclin D1 (Supplementary Figure 3a), which was predominantly confined to the cytoplasm (Schneider et al, 2008 and data not shown) and which is consistent with its function in G 1 arrest and senescence (Kortlever et al, 2006). In contrast, protein levels of the G 2 /Massociated cyclins A and B1 were strongly reduced upon prolonged TACC3 depletion (Supplementary Figure 3a), thus excluding a major contribution of the G 2 checkpoint in the post-mitotic arrest caused by TACC3 depletion.…”
Section: Resultssupporting
confidence: 72%
“…Accordingly, the p53 target gene p21 WAF , a cyclin-dependent kinase inhibitor, was efficiently induced upon TACC3 depletion, whereas expression of the p53-independent cyclin-dependent kinase inhibitor, p27 KIP , remained unchanged (Supplementary Figure 3a). Furthermore, TACC3 depletion correlated with increased levels of cyclin D1 (Supplementary Figure 3a), which was predominantly confined to the cytoplasm (Schneider et al, 2008 and data not shown) and which is consistent with its function in G 1 arrest and senescence (Kortlever et al, 2006). In contrast, protein levels of the G 2 /Massociated cyclins A and B1 were strongly reduced upon prolonged TACC3 depletion (Supplementary Figure 3a), thus excluding a major contribution of the G 2 checkpoint in the post-mitotic arrest caused by TACC3 depletion.…”
Section: Resultssupporting
confidence: 72%
“…Two other lines of evidence support the impaired ability of E6AP-deficient MEFs to undergo senescence. First, we measured the expression of two known markers of senescence: p21 and the PAI-1 (Mu and Higgins, 1995;Serrano et al, 1997;Kortlever et al, 2006). The protein and mRNA levels of p21 were higher in WT than in E6AP KO MEFs as measured by western blot analysis and by quantitative real-time PCR (qPCR), respectively ( Figure 2d).…”
Section: E6ap Is Essential For Replicative Senescencementioning
confidence: 99%
“…This suggests that PAI-1 kd or uPA overexpression induces a senescence-bypass that is not strictly cell autonomous. p53 kd MEFs have higher amounts of PAI-1 compared to PAI-1 kd cells 70 and therefore potentially lower uPA activity, and it is possible that this is why p53 kd cells were not able to immortalize fibroblasts in a paracrine fashion (Fig. 1A).…”
Section: Suppression Of Pai-1 Induces Senescence-bypass In a Paracrinmentioning
confidence: 99%
“…It should be noted however that ectopic expression of PAI-1 in immortal fibroblasts does lead to induction of senescence, consistent with the notion that PAI-1 acts downstream of p53 to block uPA activity. 70 Furthermore, we have found there is a concentration-dependent induction of senescence in immortal cells after administration of recombinant PAI-1, showing that soluble PAI-1 in culture medium is able to induce senescence (Kortlever R and Bernards R, unpublished observations). Thus, the immortalizing effects seen of PAI-1 kd are mediated, at least in part, via paracrine signaling.…”
Section: Suppression Of Pai-1 Induces Senescence-bypass In a Paracrinmentioning
confidence: 99%
See 1 more Smart Citation